2013
DOI: 10.1039/c3ta00764b
|View full text |Cite
|
Sign up to set email alerts
|

Novel DLC/ionic liquid/graphene nanocomposite coatings towards high-vacuum related space applications

Abstract: It is currently a challenge for space tribology to develop a long lifetime and high bearing capacity lubricant meeting the requirements of space applications. Herein, we dispersed graphene into ionic liquid, prepared novel composite coatings of diamond-like carbon (DLC)/ionic liquid (IL)/graphene with different graphene concentrations, and investigated its space performance under high vacuum and space radiation conditions. IL/graphene nanofluids with different concentrations were examined by Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 50 publications
2
67
0
Order By: Relevance
“…Liu et al [57], prepared DLC/IL/graphene composite coatings with different graphene concentrations, and studied their performance under high vacuum and space radiation conditions. The results showed that the addition of excess graphene to the IL would form irreversible agglomerates, finding an optimum graphene concentration of 0.075 mg mL −1 in IL for the best tribological performance in a simulated space environment.…”
Section: Thin Films and Coatingsmentioning
confidence: 99%
“…Liu et al [57], prepared DLC/IL/graphene composite coatings with different graphene concentrations, and studied their performance under high vacuum and space radiation conditions. The results showed that the addition of excess graphene to the IL would form irreversible agglomerates, finding an optimum graphene concentration of 0.075 mg mL −1 in IL for the best tribological performance in a simulated space environment.…”
Section: Thin Films and Coatingsmentioning
confidence: 99%
“…Some new nanocomposite coatings from DLC/ IL [68] or even DLC/ IL/graphene [67] combinations are being developed for space applications.…”
Section: Il Nanolubricants and Nanocoatingsmentioning
confidence: 99%
“…There still remains the field of space and vacuum tribology, where the nonvolatile nature of the ILs makes them the ideal candidates [67].…”
Section: Halogen-free Il Lubricantsmentioning
confidence: 99%
“…687 eV, which was attributed to [PF 6 ] anion. [48][49][50] These XPS spectra indicate the attachment of [PF 6 ] anions on the BNNS surfaces. In addition, the XPS surface elemental analysis for 2a (Table S2 †) shows that the F/P ratio was approx.…”
Section: Preparation Of Bnnsmentioning
confidence: 99%